2017
DOI: 10.1371/journal.pone.0174945
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy obese women have longer telomere length than obese women with metabolic syndrome

Abstract: IntroductionObesity is the principal component in the Metabolic Syndrome (MetS) that determines the progression of metabolic complications. Metabolically healthy obese (MHO) individuals seem to be protected against those complications. Telomere length (TL) as a novel marker of cellular aging had a complex relationship to the MetS. The principal aim of this study was to investigate the TL in MHO, and to study the association between TL and the worsening of the metabolic condition.Material and methodsWe have det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Moreover, in the present study, ATL was inversely correlated with BMI. This finding is consistent with several prior studies carried out by our group which showed increases in BMI and the presence of obesity as major determinants of telomere shortening [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in the present study, ATL was inversely correlated with BMI. This finding is consistent with several prior studies carried out by our group which showed increases in BMI and the presence of obesity as major determinants of telomere shortening [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…A third misconception is that obesity and chronic disease are the same phenomenon. Rather, it must be pointed out that 20% of individuals who are obese are metabolically healthy ( 7 ) with normal lifespan and health span, and expected biochemical markers of aging, such as normal length telomeres ( 8 ). Conversely.…”
Section: Introductionmentioning
confidence: 99%
“…The link between nuchal SAT accumulation, plasma insulin levels and RTL relates a specific SAT distribution pattern to an altered glucose metabolism and accelerated genomic aging, indicated by short RTL. An association between obesity and telomere physiology has been reported before 13,[30][31][32][33][34][35][36] . However, most previous studies used BMI to characterize individuals as overweight/obese or normal weight.…”
Section: Discussionmentioning
confidence: 86%